Tuning the nonlinearity of graphene mechanical resonators by Joule heating. (14th September 2022) - Suo, Jiao-Jiao; Li, Wei-Jie; Cheng, Ze-Di; Zhao, Zi-Fan; Chen, Hui; Li, Bo-Lin; Zhou, Qiang; Wang, You; Song, Hai-Zhi; Niu, Xiao-Bin; Deng, Guang-Wei
Abstract: As an inherent property of the device itself, nonlinearity in micro-/nano- electromechanical resonators is difficult to eliminate, and it has shown a wide range of applications in basic research, sensing and other fields. While many application scenarios require tunability of the nonlinearity, inherent nonlinearity of a mechanical resonator is difficult to be changed. Here, we report the experimental observation of a Joule heating induced tuning effect on the nonlinearity of graphene mechanical resonators. We fabricated multiple graphene mechanical resonators and detected their resonant properties by an optical interference method. The mechanical vibration of the resonators will enter from the linear to the nonlinear intervals if we enhance the external driving power to a certain value. We found that at a fixed drive power, the nonlinearity of a mechanical resonator can be tuned by applying a dc bias current on the resonator itself. The tuning mechanism could be explained by the nonlinear amplitude-frequency dependence theory. Our results may provide a research platform for the study of mechanical nonlinearity by using atomic-thin layer materials.